Issues and Opportunities in the Enhancement of Translation Competence Based on a Student-Centred Approach - Go'zal Abdupattahovna Khalilova (Psychohealth: Scientific Journal of Psychology and Mental Health, 2026)
Purpose: This study investigates the enhancement of translation competence through a learner-centred approach, focusing on linguistic, intercultural, communicative, strategic, and instrumental components. It also identifies key challenges, including individual differences, motivation, practical skill development, and cultural understanding. Methodology: A learner-centred pedagogical framework was applied, integrating differentiated instruction, reflective practice, project-based learning, and modern technological tools. Experimental observation and performance assessment evaluated the effectiveness of these strategies in improving translation competence.Results: The study found that learner-centred instruction significantly improves translation quality, professional competence, and intercultural awareness. Students demonstrated enhanced application of pragmatic and linguistic skills, increased engagement, and improved independent problem-solving and reflective thinking.Conclusions: Implementing a learner-centred approach effectively develops comprehensive translation competence by combining cognitive, pragmatic, and intercultural learning. Reflective and project-based activities, along with technology, foster skill development and cultural understanding.Limitations: The study was conducted in a controlled educational setting with a limited sample, which may affect generalizability. Only specific language pairs were tested, and long-term skill retention was not assessed. Future research should explore larger, more diverse samples and multiple language contexts.Contributions: This article provides evidence-based strategies for translation pedagogy, highlighting learner-centred instruction, reflective practice, and technology integration to prepare translators for complex linguistic and intercultural challenges.